J’ai tout le temps aimé expand mes horizon: A Closer Look at the Insertion of English-Origin Lexical Verbs in Louisiana French - Root, Jamie (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
While the treatment of English-origin lexical verbs inserted into Louisiana French has received some attention, relatively little research has specifically targeted these forms. Most studies have focused on their occurrence in naturalistic data, a practice that risks providing only a partial understanding of the lexical insertion strategies of speakers. This study examines the morphological treatment of two categories of English-origin verbs across six different morphological contexts using elicited data. These data confirm that the use of bare forms remains the most frequently employed lexical insertion strategy, but they also show that lexical insertion in Louisiana French is far from uniform. Moreover, although factors such as listedness (relative frequency) and finiteness have been proposed as predictors of morphological integration in other language contact situations, these predictors do not account for the patterns observed in Louisiana French.